Der Dialog nach Art. 17 III AEUV: "In Anerkennung ihrer Identität und ihres besonderen Beitrags" - Schnabel, Patrick Roger (Jus Ecclesiasticum, 2014)
The author examines the dialogue between the EU and churches/religious communities according to Art. 17 III TFEU. He analyses its difference from the dialogue with civil society according to Art. 11 TEU, showing that in making this distinction, the EU respects the specific character of such organisations. Both dialogues, however, open the EU to the multiple facets of society, overcoming a mere economic approach to integration.